LEGAL POLICY AND ITS POSITION IN THE TAXONOMY OF SCIENCE - Wahju Prijo Djatmiko (Jurnal Dinamika Hukum, 2018)
Legal Policy is a new study and part of constitutional law (Staatrecht). Legal Policy is derived from two disciplines which are the Science of Law and the Philosophy of Law. Thus, it is not an intersection between the science of Law and Politics. Legal Policy operates on an empirically functional level using the teleological constructive method. This implies that politics is in the sense of ethics and the techniques of forming law (rechtsvorming) and law discovery (rechtsvinding). From the ontological and epistemological aspects,  Legal Policy  has a very strong root to be included in the science of law because its core is laws of legislation in various forms and levels. Legal Policy provides an academic basis for the process of formation and discovery which is in line with welfare, circumstances, culture, and existing values in society. Keywords: legal policy, rechtvinding, rechtsvorming, taxonomy